2021
DOI: 10.36103/ijas.v52i4.1399
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Traits of Local Mountain Goat and Some Factors Affecting Them

Abstract: The aim of the current investigation was to evaluate some reproductive aspects of local mountain goat raised in farm conditions. A total number of 498 does were mated during two successive years. Results revealed that fertility, conception, kidding, productivity and twinning rates averaged 80.72, 87.15, 84.94, 72.29 and 5.22 %, respectively. Litter size at birth and weaning were 1.05 and 0.9 respectively. Also, all above traits were significantly lower in does aged 2.5 years as compared with older does except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…The unique and densely layered arrangement of capillaries beneath the lamina epithelialis in the bovine cauda epididymidis provided a strong morphological basis for intensive metabolic processes [25] Bucks were considered as seasonal breeders being short or long day breeders, the sexual activity of the bucks varies among breeds and the animal's geographical location [33]; [34]; [35] The researches of the animals management mentioned that the optimum seasonality was seen in late summer and autumn [36]; [37]). Furthermore, some studies on Meriz bucks indicated that the highest rates of reproduction occurred in August followed by September [38].Histomorphometric and histochemical of our studies documented that the breeding season occurred in autumn particularly in October. Our disagreement with the researchers above was attributed to the impact of global warming on some countries worldwide including Iraq [39]This phenomenon had affected the seasonality of mating, as previously, two decades ago, matting occurred at the end of summer and beginning of autumn.…”
Section: Discussionsupporting
confidence: 59%
“…The unique and densely layered arrangement of capillaries beneath the lamina epithelialis in the bovine cauda epididymidis provided a strong morphological basis for intensive metabolic processes [25] Bucks were considered as seasonal breeders being short or long day breeders, the sexual activity of the bucks varies among breeds and the animal's geographical location [33]; [34]; [35] The researches of the animals management mentioned that the optimum seasonality was seen in late summer and autumn [36]; [37]). Furthermore, some studies on Meriz bucks indicated that the highest rates of reproduction occurred in August followed by September [38].Histomorphometric and histochemical of our studies documented that the breeding season occurred in autumn particularly in October. Our disagreement with the researchers above was attributed to the impact of global warming on some countries worldwide including Iraq [39]This phenomenon had affected the seasonality of mating, as previously, two decades ago, matting occurred at the end of summer and beginning of autumn.…”
Section: Discussionsupporting
confidence: 59%